Early Neonatal Mortality and Predictors in Newborns Admitted to the Neonatal Intensive Care Unit at Public Hospitals in Hadiya Zone, Central Ethiopia: A Retrospective Cohort Study - Desta Osamo Kelbore MPH; Dejene Ermias Mekango MPH; Tegegn Tadesse Arficho MSc; Bisrat Feleke Bubamo MPH; Desta Erkalo Abame MPH (SAGE Publishing, 2024)
Background . Despite numerous life-saving measures, neonatal mortality remains high. This research aims to investigate the incidence and predictors of early neonatal mortality among newborns admitted to intensive care units in public hospitals in Hadiya Zone, Ethiopia. Methods . A retrospective cohort study was conducted on 689 neonates admitted to the neonatal intensive care unit. Cox proportional hazard regression by STATA was used. Results . This study followed for 3439 person-days found an incidence rate of 16.9 deaths per 1000 person-days. Birth weight [AHR = 4.4, 95% CI; 1.29, 14.94], APGAR score at the fifth minute 4 to 6 [AHR = 0.42, 95% CI; 0.2, 0.87], hypoglycemia [AHR = 8.1, 95% CI; 2.17, 30.43], no treated with oxygen [AHR = 2.6, 95% CI; 1.1, 5.9], and obstetric complications [AHR = 0.41, 95% CI; 0.18, 0.93] predicted early neonatal mortality. Conclusion . The study revealed a high neonatal mortality rate, necessitating increased focus on oxygen treatment for newborns and improved early diagnosis and treatment of obstetric complications.